2022
DOI: 10.1038/s41467-022-34284-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of organic cation transporter-3 inhibition

Abstract: Organic cation transporters (OCTs) facilitate the translocation of catecholamines, drugs and xenobiotics across the plasma membrane in various tissues throughout the human body. OCT3 plays a key role in low-affinity, high-capacity uptake of monoamines in most tissues including heart, brain and liver. Its deregulation plays a role in diseases. Despite its importance, the structural basis of OCT3 function and its inhibition has remained enigmatic. Here we describe the cryo-EM structure of human OCT3 at 3.2 Å res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…All prominent differences in transport kinetics identified here were differences in the maximum transport rate (Figures , , and and Table S1). Although with the recent cryo-EM data, ,, we have much better structural insights into the OCTs than before, we still do not understand all aspects of the transport processes. We may speculate that the maximum transport rate is not (or not only) correlated with a high binding affinity to the transporter in the outward-open configuration but with rapid substrate release from the inward-open configuration.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…All prominent differences in transport kinetics identified here were differences in the maximum transport rate (Figures , , and and Table S1). Although with the recent cryo-EM data, ,, we have much better structural insights into the OCTs than before, we still do not understand all aspects of the transport processes. We may speculate that the maximum transport rate is not (or not only) correlated with a high binding affinity to the transporter in the outward-open configuration but with rapid substrate release from the inward-open configuration.…”
Section: Discussionmentioning
confidence: 90%
“…However, mutagenesis studies of OCT1 demonstrated that single amino acids can completely determine a transporters’ stereoselectivity . Although this has not been shown for OCT2 and OCT3 yet, the revolution of structural biology by the improvements in cryogenic electron microscopy (cryo-EM) has just affected the OCT field. , High-resolution structural data might accelerate the identification of amino acids determining the stereoselectivity of OCT2 and OCT3 by computationally guided biochemical studies. The frequent naturally occurring genetic variants studied here did not affect the transporters’ stereoselectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal microscopy and image analysis. Confocal microscopy and image analysis was conducted as previously described [32]. In brief, cells expressing yellow fluorescent protein(YFP)-tagged human SERT or DAT, respectively, were seeded on PDL-coated 35 mm glass-bottom dishes 24 h before image acquisition.…”
Section: -Ht Receptor-dependent Induction Of Gcamp6 Fluorescence In H...mentioning
confidence: 99%